Effect of Chicken Manure, Husk Charcoal on Growth, Production, P Availability of Shallot in Rice Fields - Panjaitan, Ernitha; Manalu, Chici Josephine; Sidauruk, Lamria; Sianipar, Ebsan (CV. Rayyan Dwi Bharata, 2023)
The study aims to find out the impact of poultry and coal fertilization on the growth, production and availability of P on red onions in savage land. The study used a random group plan (RAK) with two treatment factors. Chicken cage fertilizer factor and coal coal factor use each 4 levels. The results of the study showed that the dose of real chicken cage fertilizer up to a dose of 7.5 kg/plot improved the length of the leaves, the wet weight of the bulbs/plots, the Wet Weight of the plots/bulbs, the dry weight of plants/bubbles, the Dry Weight and Root Volume, the soil content, the saturation of the base, C-organic soil, soil pH and the availability of soil P, having no real impact on the amount of bulbs. The supply of coal to a dose of 5.7 kg/plot did not have a tangible effect on all the same parameters observed with the administration of poultry cage fertilizer doses. The interaction between the dosage of chicken cage fertilizer and coal has no tangible effect on all the observed parameters.